Days of wine and roses - Edwards, Blake, 1922-; Manulis, Martin, 1915-; Miller, J. P. (James Pinckney), 1919-; Mancini, Henry; Lemmon, Jack.; Remick, Lee.; Bickford, Charles, 1889-1967.; Klugman, Jack.; Hewitt, Alan, 1915-1986.; Palmer, Tom.; Warner Bros. Pictures (1923-1967); Warner Home Video (Firm) ([United States] : Warner Home Video, 2004)
A domestic drama which reveals the corrosive effects of alcoholism on a hardened young advertising executive and his attractive young wife, both of whom drink heavily to compensate for their insecurity.
Originally released as a motion picture in 1962.
Based on the television play by J.P. Miller.
Special features include: commentary by director Blake Edwards, vintage Jack Lemmon interview, theatrical trailers.
Music, Henry Mancini ; photography, Phil Lathrop ; editor, Patrick McCormack.
Jack Lemmon (Joe), Lee Remick (Kirsten), Charles Bickford (Arnesen), Jack Klugman (Jim Hungerford), Alan Hewitt, Tom Palmer.
MPAA rating: Not rated.
Keywords: Alcoholics -- Drama; DVD's.; DVD-Video discs; Video recordings; Feature films; Video recordings for the hearing impaired